Perceptual responses of (sports-)clothing-body interaction simulating pre- and post-purchase experience - Julia Wilfling; George Havenith; Margherita Raccuglia; Simon Hodder (Communications in Development and Assembling of Textile Products, 2023)
The appreciation of textile products highly depends on a satisfactory ‘feel’ in fabric-skin contact. The question arising is whether the haptic interpretation of a garment (by hand) is comparable to a feeling produced when it is donned or used in its intended application. Sports T-shirts made from three different fiber types (CO, PES I, PES II) were studied in a pre- and post-purchase scenario by exposing 20 female participants to a hand, a donning (pre-purchase) and running evaluation (post-purchase) in 22 °C and 50% relative humidity (RH). Objective measurements such as skin temperatures, heart rate, body sweat loss, and sweat absorption of the garments were recorded. Subjective data was collected during the fabric hand and the donning evaluation as well as within the running protocol after 5 min, 20 min, and 5 min of cool down. Perceptual responses to 12 hand-/skin-feel descriptors (e.g., rough, smooth) were rated on a scale from 0 (not at all) to 10 (completely) and a feeling of discomfort was given. No significant differences between a hand and a donning evaluation were found in the rating of the sensations. The hand evaluation provided sufficient information for a comfort response to garment wear. The pre- and post-purchase comparison found a significantly lower perception of the feeling of roughness whilst running with the CO shirt and smoothness during running in PES II. The stickiness and comfort perception increased significantly in the post-purchase wear trial. Hence, moisture on the skin provoked through running influences comfort characteristics as well as the perception on haptic cues in t-shirts. Especially surface related haptic characteristics e.g., roughness and smoothness, are reduced.